(untitled) (Research, Society and Development, 2021)
Introduction: The parental responsibility of parents regarding the feeding of children implies having a responsible job when selecting, preparing and offering food to their children; in addition, qualities of exemplary behavior such as healthy eating behavior that influences the habits that their children acquire; however, there are multiple determining factors that negatively affect it. Objective: To identify the determining factors in the parental responsibility of caregivers to promote an eating behavior in children from 6 months to 12 years old. Methods: The review will be carried out according to the methodology proposed by Hilary Arksey and Lisa O`Malley updated by The Joanna Briggs Institute (JBI) for scoping review. A comprehensive search strategy will be applied with the support of the research librarian to refine the search and locate the studies. Inclusion criteria of quantitative, qualitative and mixed studies will be applied, in titles, abstract and full text; Two reviewers will independently extract the information using a screening tool; finally, the results will be presented narratively and tables or figures will be used. Ethics and disclosure: This scoping review will involve a secondary analysis of the data already collected and therefore does not require ethical approval. The results of this research will be submitted to peer-reviewed journals for publication and will also be disseminated at conferences and seminars.